2014
DOI: 10.1037/ort0000005
|View full text |Cite
|
Sign up to set email alerts
|

Consensus statement on group care for children and adolescents: A statement of policy of the American Orthopsychiatric Association.

Abstract: Group care for children and adolescents is widely used as a rearing environment and sometimes used as a setting in which intensive services can be provided. This consensus statement on group care affirms that children and adolescents have the need and right to grow up in a family with at least 1 committed, stable, and loving adult caregiver. In principle, group care should never be favored over family care. Group care should be used only when it is the least detrimental alternative, when necessary therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
65
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(67 citation statements)
references
References 49 publications
0
65
0
2
Order By: Relevance
“…Nevertheless, this analysis suggests that life in institutions does not favor recovery, whereas moving into adoptive or foster care families can lead to a significant (although not always complete) recovery (van den Dries et al, 2009). Despite all the evidence and recommendations (Dozier et al, 2014;Unicef, 1989), a lot of work remains to be done to ensure that children actually are moved into a sensitive family-environment in the absence of a stable and caring biological family. The high prevalence of insecure and disorganized rates identified in children reared in institutions requires attention not only to improve the current quality of children's development but also because of long-term consequences that non-secure patterns, especially the disorganized pattern, have on subsequent development in terms of negative social-emotional outcomes (Pasco Fearon & Belsky, 2011;Lyons-Ruth & Jacobvitz, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this analysis suggests that life in institutions does not favor recovery, whereas moving into adoptive or foster care families can lead to a significant (although not always complete) recovery (van den Dries et al, 2009). Despite all the evidence and recommendations (Dozier et al, 2014;Unicef, 1989), a lot of work remains to be done to ensure that children actually are moved into a sensitive family-environment in the absence of a stable and caring biological family. The high prevalence of insecure and disorganized rates identified in children reared in institutions requires attention not only to improve the current quality of children's development but also because of long-term consequences that non-secure patterns, especially the disorganized pattern, have on subsequent development in terms of negative social-emotional outcomes (Pasco Fearon & Belsky, 2011;Lyons-Ruth & Jacobvitz, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized study (Nelson et al, 2007), it was subsequently confirmed that placement in alternative family settings such as foster care is better for adequate child development than placement in orphanages and institutional settings. Recently, a team of renowned experts on child development, in conjunction with the American Orthopsychiatry Association, published a consensus statement on group care contexts affirming the right of children to grow up in a family setting (Dozier et al, 2014). However, even though most countries recognize that being placed in an institution is not the best practice for the child's wellbeing, institutionalization continues to be an option (Engle et al, 2011,Soares et al, 2014, and child neglect in general remains a global phenomenon of considerable extent (Stoltenborgh, Bakermans-Kranenburg, & van IJzendoorn, 2013, Stoltenborgh, Bakermans-Kranenburg, Alink, & van IJzendoorn, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Dozier et al (2014) has also published an article titled "Consensus statement on group care for adolescents". This is a policy statement that claims that, Group care should be used only when it is the least detrimental alternative, when necessary therapeutic mental health services cannot be delivered in a less restrictive setting.…”
Section: Introductionmentioning
confidence: 99%
“…Results highlight the importance of the family in providing a consistent, privileged, and secure relationship, which is essential in sensitive periods of socioemotional development (Julian & McCall, ). In the Portuguese context, nearly 97% of children who cannot remain in their birth family are placed in institutional care, which is not only an anomaly in Western countries today (Del Valle & Bravo, ) but also a context that cannot provide the type of attachment relationship with a caregiver that young children need (Dozier et al, ). Family alternatives should be promoted, particularly for young children.…”
Section: Discussionmentioning
confidence: 99%